(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The introduction of 5G technology, which will alter how the majority of high-bandwidth users use their phones, was are subject of this study. The author spoke about the early iterations of the communications technology that was looked at, as well as how connection, presentation, benefits, and limitations progressed. Cloud management is used for the connectivity of the data in the structure the author developed, which was developed using many new generations of wireless media that have evolved and advanced in wireless communication technology as well as their numerous different benefits and advantages. The findings demonstrate that the structure is built in a way that, with the aid of the internet of things (IoT) and 5G technology, the absence of data modules will be collected in it. The author comes to the conclusion that as wireless communication gained strength and efficiency, it paved the path for the creation of mobile phone technology, which is currently widely utilized. This study has the ability to be employed in the fundamental framework of the system and is readily disposable.